+0  
 
0
182
5
avatar

(-125)^1/3

Guest Mar 18, 2018
 #1
avatar+605 
+1

sorry I misread the question

gueesstt  Mar 18, 2018
edited by gueesstt  Mar 18, 2018
 #2
avatar
+1

Simplify the following:

(-125)^(1/3)

 

(-125)^(1/3) = (-1×125)^(1/3) = (-1×5^3)^(1/3):

(-5^3)^(1/3)

 

(-5^3)^(1/3) = (-1)^(1/3) (5^3)^(1/3) = (-1)^(1/3)×5^(3/3) = (-1)^(1/3)×5:

 

5(-1)^(1/3)

Guest Mar 18, 2018
 #5
avatar+93627 
+2

Here is a correction to you answer guest :)

 

Simplify the following:

(-125)^(1/3)

 

(-125)^(1/3) = (-1×125)^(1/3) = (-1×5^3)^(1/3):

(-5^3)^(1/3)

 

(-5^3)^(1/3) = (-1)^(1/3) (5^3)^(1/3) = (-1)^(1/3)×5^(3/3) = (-1)^(1/3)×5:

 

= -1*5

= -5

 

(-1)^(1/3) = -1 becasue  (-1)^3=-1

Melody  Mar 18, 2018
 #3
avatar+753 
+1

-41.6666666667

Lightning  Mar 18, 2018
 #4
avatar+93627 
+3

(-125)^1/3

 

since 

 (-5)^3=-125

 

(-125)^(1/3) = -5    

Melody  Mar 18, 2018

41 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.